2021
DOI: 10.1111/ele.13732
|View full text |Cite
|
Sign up to set email alerts
|

Macrogenetic studies must not ignore limitations of genetic markers and scale

Abstract: Millette et al. (Ecology Letters, 2020, 23:55-67) reported no consistent worldwide anthropogenic effects on animal genetic diversity using repurposed mitochondrial DNA sequences. We reexamine data from this study, describe genetic marker and scale limitations which might lead to misinterpretations with conservation implications, and provide advice to improve future macrogenetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 11 publications
1
36
1
Order By: Relevance
“…A second study found no significant trends between the current amount of human impact in a given area and the diversity in the mitochondrial cytochrome c oxidase subunit I (COI) gene of a wide variety of bird, fish, insect, and mammal species (Millette et al, 2020). The lack of signal of this study could be due to the gene studied (Paz-Vinas et al, 2021), which is under purifying selection (Pentinsaari et al 2016), and then may not capture genome-wide neutral diversity (Kardos et al, 2021). Rather than a temporal study, Millette et al's resembles a sensitivity analysis, where one may expect areas that have been more disturbed historically by humans will have lower levels of genetic diversity.…”
Section: V5 Ongoing Efforts In Characterizing Genetic Diversity Losscontrasting
confidence: 54%
“…A second study found no significant trends between the current amount of human impact in a given area and the diversity in the mitochondrial cytochrome c oxidase subunit I (COI) gene of a wide variety of bird, fish, insect, and mammal species (Millette et al, 2020). The lack of signal of this study could be due to the gene studied (Paz-Vinas et al, 2021), which is under purifying selection (Pentinsaari et al 2016), and then may not capture genome-wide neutral diversity (Kardos et al, 2021). Rather than a temporal study, Millette et al's resembles a sensitivity analysis, where one may expect areas that have been more disturbed historically by humans will have lower levels of genetic diversity.…”
Section: V5 Ongoing Efforts In Characterizing Genetic Diversity Losscontrasting
confidence: 54%
“…For example, the stalked barnacle (Watanabe et al, 2018) possesses distinct morphotypes along the CIR, but whether these morphological variations are the results of phenotypic plasticity or genetic differentiation between populations is unknown. The stalked barnacle did not appear to be genetically different across vent fields, but their phylogenetic relationship was assessed only by using the mitochondrial COI gene, which is not good enough to discriminate closely related populations (Paz-Vinas et al, 2021).…”
Section: Community Differences Across Vent Fieldsmentioning
confidence: 99%
“…Furthermore, measures of genetic variation are often used to assess a species' or population's ability to respond to environmental (climate, habitat, biotic) changes (Frankham 2005;Hoffman and Sgró 2011), so large-scale analyses such as this, allow for targeting individual species that might be at a higher risk for extinction (Frankham et al 2014;Hoban et al 2020) and for identifying species attributes that contribute to higher levels of genetic diversity (Broadhurst et al 2017). While there is no consensus as to whether measures of genetic diversity from a single mitochondrial or chloroplast gene, the most common in our dataset, are appropriate measures of genetic diversity (Petit-Marty et al 2021;Paz-Vinas et al 2021), many species (15%; 13,960 total) have data from multiple loci in phylogatR and measures of genetic diversity across loci can be evaluated.…”
Section: Empirical Examplementioning
confidence: 99%